Proposed English education materials for Muslim literary critics - Mohd Ramli, Aimillia (2013)
The objective of this paper is to suggest a new framework for the study of English literature that integrates scientific and humanistic philosophical approaches. It centralizes the spiritual development of literary students as critics of literature by approaching literary works from a Tawhidic perspective. This framework involves the application of Quranic verses and hadith as well as the Islamic philosophies of several Muslim figures, notably Syed Muhammad Naquib al-Attas and Muhammad Iqbal, on a number of issues, such as intuition, free-will and happiness. These will then be subjected to comparative analyses of English and Islamic literature by writers and poets who propagate their philosophies in their works. Other methods used will be the comparative religion framework, particularly for English literary works that deal with Christianity. By locating literature as having a role in Western-Islamic comparative studies of concepts and beliefs, this paper suggests a new education and role for future literary critics as those who would be engaged in literary appreciation while propagating a Tawhidic outlook on life.